Phytochemical screening and wound healing effect of Alocasia longiloba Miq. petiole ethanolic extract and its fractions in excision wound rat model - Che Hamzah, Nurul Hazirah; Mohammed, Arifullah; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Hamzah, Zulhazman; Lee, Seong Wei (Penerbit UMS, 2022)
Alocasia longiloba Miq., or ‘keladi candik’ is traditionally used for wound healing in Malaysia. Preliminary studies have been performed to determine the dose range of A. longiloba for potential wound healing. Therefore, this study continues to determine the phytochemical screening of fractions and their ability in accelerating wound healing. Ethanol crude extract of A. longiloba and its fractions of hexane, chloroform, and ethyl acetate was prepared and used for phytochemical screening and wound healing formulation. Seven groups of Sprague-Dawley rats (n = 3) were experimentally wounded in the dorsal area for 12 days. Group I was left untreated, Group II was dressed in petroleum jelly as the vehicle group, Group III was treated with Solcoseryl jelly 10% as the positive drug, and the rest of the groups were dressed with respective formulations at 6% concentration. The wound area was photographed and measured, and the histological examinations of granulation tissues were examined. The phytochemical screening of chloroform fraction shows an abundance of alkaloids, flavonoids, and tannins, which are considered responsible for wound healing activity. The chloroform fraction proved more effective, showing a significant percentage of wound contraction (p<0.05) compared to the negative and vehicle control groups. Moreover, histological observation of wounds treated with chloroform fraction of A. longiloba showed an organized epithelial layer, fewer blood vessels, and dense collagen fibres comparable with normal rat skin.